Swedish - Finnish glossary: custody enquiry - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with custody enquiry words. Published in Kieliviesti 4/2007. Contains approximately 150 entries. 2007.

Svensk-sverigefinsk ordlista med vårdnadsutredningsord. Publicerades i Kieliviesti 4/2007. Innehåller ca 150 ord. 2007.
Svensk-finsk ordlista: vårdnadsutredning
Keywords: law; juridik; Child Custody; Barnförmynderskap; Dissent and Disputes; Oenighet och tvister; litigation; rättstvist; child; barn; children's rights; barns rättigheter; word list; ordlista; Language and linguistics; Språk och lingvistik; Legislation and legal systems; Lagstiftning och rättssystem; Languages and Literature; Språk och litteratur; Other Legal Research; Annan rättsvetenskaplig forskning